Missed Island: The Impact Of Local Community Resistance In The Postcovid-19 Era In Bali - Wahyu Kusuma, Irawinne Rizki (Akademi Komunitas MAPINDO, 2022)
Jurnal Manajemen Pelayanan Hotel Akademi Komunitas Manajemen Perhotelan Indonesia (Kusuma, halaman 603-615) Vol 6, No 2 Edisi Desember 2022 603 Missed Island: The Impact Of Local Community Resistance In The Postcovid-19 Era In Bali Irawinne Rizki Wahyu Kusuma Akademi Komunitas Manajemen Perhotelan Indonesia, Bali, Indonesia winerichie88@gmail.com Abstract The local community's ability to survive the onslaught of the pandemic that has hit almost 3 years has made the economy decline, which can be seen from the sluggish tourism. The local community in Bali made a breakthrough by carrying the theme ‘KemBALI Becik’. The statement of to return back better indicating that there will be fresh air that will stimulate the pace of tourism. The resistance described here is the ability to survive and build an innovation in the future for the advancement of the tourism sector. Bali, which has long been known for its nature, local culture and tourism destinations, no longer touches only traditions but extends to modernity. The development of tourist villages that is carried out continuously, slowly and sustainably will gradually increase the area of tourism destinations in every area in Bali. According to the 2022 Bali Summit, the G20 plays a role in other international concerns such as trade, climate, and development. The G20 also played an important role in supporting the 2030 Agenda for Sustainable Development. This research is a qualitative descriptive with a critical constructivist paradigm, the phenomenon being studied is socially constructed. Keywords: Local Community, Resistance, Postcovid-19 Era, Sustainability, G20.